Effects of acute and chronic beta-receptor blockade on ventricular repolarisation in man. Issue 6 (June 1981) - Edvardsson, N; Olsson, S B
Abstract : The right ventricular repolarisation phase was studied electrophysiologically after an injection of 15 mg metoprolol in 16 healthy volunteers. Eight of them were restudied after chronic treatment with 400 mg metoprolol daily for five weeks. The assessment of the repolarisation time included ventricular effective refractory periods, monophasic action potential duration, and the QT interval measured during atrial stimulation at different driving frequencies. The acute administration of 15 mg metoprolol intravenously had no detectable effect on the repolarisation phase, while chronic treatment caused a significant increase of the ventricular effective refractory periods, monophasic action potential duration, and the QT interval during atrial stimulation. Thus the study confirmed the contrasting effect of acute and chronic beta-receptor blockade on the ventricular repolarisation time in man.